Perancangan Enterprise Architecture Pada Bidang Sumber Daya Manusia Dan Organisasi Serta Bidang Komunikasi Hukum Dan Administrasi Pt Pln Distribusi Jawa Barat Menggunakan Framework Togaf Adm - Ersa Novia Fajrin; Yuli Adam Prasetyo; Faishal Mufied Al Anshary (eProceedings of Engineering, 2016)
PLN Distribusi Jawa Barat is the largest State Electric Service Unit in the State Indonesia. Operational flow of electricity in Provinsi Jawa Barat was given to Kantor Distribusi Jawa Barat (PLN DJB). To enhance the corporate image required employees who have potential and considerable development work in both. Additionally PLN DJB should facilitate infrastructure that can support the needs of enterprise employee performance when work . Because of the company making educational programs, provide welfare for employees and facilitate the company to the employee. Therefore, Minister for Human Resources and Organization and Communication Sector, Law and Administration should align business strategy that has been applied to the development of technology. One method of aligning business strategy and information technology that is the Enterprise Architecture (EA). There is a framework that can be used as a reference for designing Enterprise Architecture, the TOGAF ADM. TOGAF ADM consists of 9 phases preliminary phase, architecture vision, business architecture, information systems architecture, technology architecture, opportunities and solutions, migration planning, implementation governance and change management architecture. This research takes a case study in the Field of Human Resources and Organization and Communication Sector, Law and Administration PLN DJB using the preliminary phase to phase opportunities and solutions to produce a draft roadmap. Keywords: Enterprise Architecture, Energy Company, TOGAF ADM